Differences Between Standard and Sport-Specific Countermovement Jumps in High-Performance U18 Male Water Polo Players: A Cross-Sectional Study - Băltean, Alexandru Ioan; de Hillerin, Pierre Joseph; Geantă, Vlad Adrian (Stadium - Hungarian Journal of Sport Sciences, 2025)
Introduction: Vertical jump capacity is essential for evaluating lower-limb performance in water polo, especially under dryland testing conditions. While power or force is often implied, jumping height remains the primary measurable outcome in these protocols. Aim: This study aimed to compare vertical jump performance in U18 male water polo players using two jump types: the standard Counter-movement Jump (CMJ) and a modified "Frog Style" CMJ (CMJ-Frog), hypothesizing that the latter better reflects sport-specific lower-limb mechanics. Materials & Methods: A cross-sectional, within-subjects design was employed on a sample of 39 male water polo players from the Under-18 category (mean height: 183.02 ± 5.43 cm; mean weight: 75.20 ± 10.41 kg). Each athlete performed three maximal trials of two jump protocols: the standard Counter-movement Jump (CMJ) and the modified sport-specific CMJ-Frog. Jump height was measured using the OptoJump Next system. Data analysis comprised descriptive statistics and normality assessment using the Kolmogorov–Smirnov test. Inferential statistics were conducted via paired-samples t-tests to compare protocols within subjects, with effect sizes calculated using Cohen’s d. Results: CMJ-Frog jumps yielded significantly higher values (37.43 ± 4.59 cm) than standard CMJs (34.17 ± 4.49 cm), t (38) = -7.46, p < .001, with a large effect size (d = 1.19). Conclusions: The CMJ-Frog style may serve as a more functionally relevant assessment for evaluating vertical jump capacity in Under-18 male water polo players, as it better reflects the mechanics of aquatic elevation during gameplay. It may offer a more specific alternative for performance testing and monitoring in aquatic athletes. Future studies should validate the CMJ-Frog protocol in senior players and investigate its relationship with in-water performance metrics.